90.8k views
3 votes
Enter the value of x! Thank you!

Enter the value of x! Thank you!-example-1

2 Answers

5 votes

Explanation:


</p><p>\underline{\bf{Given\::}} </p><p>Given:</p><p> </p><p> </p><p></p><p></p><p></p><p>\underline{\bf{To\:find\::}} </p><p>Tofind:</p><p> </p><p> </p><p></p><p></p><p>\underline{\bf{Explanation\::}} </p><p>Explanation:</p><p> </p><p> </p><p></p><p></p><p>\boxed{\bf{(1)/(f) =(1)/(v) -(1)/(u) }}}}</p><p></p><p>\begin{gathered}\longrightarrow\sf{(1)/(-10) =(1)/(v) -(1)/(-30) }\\\\\\\longrightarrow\sf{(1)/(v) =(1)/(-10) +(1)/(30) }\\\\\\\longrightarrow\sf{(1)/(v) =(-3+1)/(30) }\\\\\\\longrightarrow\sf{(1)/(v) =\cancel{(-2)/(30) }}\\\\\\\longrightarrow\sf{(1)/(v) =(1)/(-15) }\\\\\\\longrightarrow\sf{v=-15\:cm}\end{gathered} </p><p>⟶ </p><p>−10</p><p>1</p><p> </p><p> = </p><p>v</p><p>1</p><p> </p><p> − </p><p>−30</p><p>1</p><p> </p><p> </p><p>⟶ </p><p>v</p><p>1</p><p> </p><p> = </p><p>−10</p><p>1</p><p> </p><p> + </p><p>30</p><p>1</p><p> </p><p> </p><p>⟶ </p><p>v</p><p>1</p><p> </p><p> = </p><p>30</p><p>−3+1</p><p> </p><p> </p><p>⟶ </p><p>v</p><p>1</p><p> </p><p> = </p><p>30</p><p>−2</p><p> </p><p> </p><p> </p><p> </p><p>⟶ </p><p>v</p><p>1</p><p> </p><p> = </p><p>−15</p><p>1</p><p> </p><p> </p><p>⟶v=−15cm</p><p> </p><p> </p><p></p><p></p><p>\boxed{\bf{M \:A \:G \:N\: I \:F \:I \:C\: A\: T \:I \:O\: N :}} </p><p>MAGNIFICATION:</p><p> </p><p> </p><p></p><p>\begin{gathered}\mapsto\sf{m=(Height\:of\:image\:(I))/(Height\:of\:object\:(O)) =(Distance\:of\:image)/(Distance\:of\:object) =(v)/(u) }\\\\\\\mapsto\sf{m=\cancel{(-30)/(-15)} }\\\\\\\mapsto\bf{m=2\:cm}\end{gathered} </p><p>↦m= </p><p>Heightofobject(O)</p><p>Heightofimage(I)</p><p> </p><p> = </p><p>Distanceofobject</p><p>Distanceofimage</p><p> </p><p> = </p><p>u</p><p>v</p><p> </p><p> </p><p>↦m= </p><p>−15</p><p>−30</p><p> </p><p> </p><p> </p><p> </p><p>↦m=2cm</p><p> </p><p> </p><p></p><p>Thus;</p><p></p><p>The magnification will be 2 cm .</p><p></p><p>

User Audriana
by
4.7k points
3 votes

Answer:

x = 3

Explanation:

given:

f(x) = g(x)

f(x) = x³ - 3x² + 2

g(x) = x² - 6x + 11

find: the value of x

solution:

  • as given f(x) = g(x)
  • equate each side x³ - 3x² + 2 = x² - 6x + 11
  • combine similar terms and equate to zero: x³ - 4x² + 6x - 9 = 0
  • solve by factoring: (x - 3) (x² - x + 3)
  • use the Zero factor principle: x - 3 = 0
  • x = 3
  • for x² - x + 3 = 0 ----this is a complex solution.

therefore, the value of x = 3

User Keshav Vishwkarma
by
4.7k points